Evaluation on the equivalence between the backward/forward iterative sweep and the triangular-based power flow methods in electrical distribution networks - Oscar Danilo Montoya-Giraldo; Walter Gil-González; Edwin Rivas-Trujillo (Revista UIS Ingenierías, 2024)
This paper demonstrates that graph-based power flow methods for strictly radial distribution networks (one based on the upper-triangular matrix and the other on the incidence matrix or classical backward/forward power flow method) are equivalent, implying that both recursive power flow formulas are the same. A small distribution network composed